Perception of failure in a sample of chilean entrepreneurs (Gestión y Gerencia, 2026)
This research consists in the presentation of the results of a survey applied to a sample of entrepreneurs about their perception of failure. About the steps developed for its execution, first, a bibliographic review was carried out in relation to the concepts of failure, perception and entrepreneurship. Subsequently, an instrument was developed to measure perception of failure in entrepreneurs. As a third step, the survey was validated by actors in the entrepreneurship ecosystem. As a fourth step, once the instrument was validated, it was applied to a sample of entrepreneurs in Chile. The final stage corresponds to the analysis of results which are described in this publication.
Keywords: Entrepreneurship; failure; perception